The Management of Cytokine Storm in COVID-19 - Cleopas Martin Rumende; Erwin C Susanto; Truely P Sitorus (Acta Medica Indonesiana)
Cytokine storm in COVID-19 infection is an excessive immune response to external stimuli where the pathogenesis is complex. The disease progresses rapidly and the mortality is high. Certain evidence shows that the severe deterioration of some patients has been closely related to the strong upregulation of cytokine production in SARS-Co-V2 induced pneumonia with an associated cytokine storm syndrome. Identification of existing approaved therapy with proven safety profile to treat hyperinflammation is critical unmet need in order to reduce COVID-19 associated mortality. To date, no specific therapeutic drugs are available to treat COVID-19 infection. Preliminary studies have shown that immune-modulatory or immune suppressive treatments might be considered as treatment choices for COVID-19, particularly in severe disease. This article review the pathogenesis and treatment strategies of COVID-19 virus-induced inflammatory storm in attempt to provide valuable medication guidance for clinical treatment.